Synthesis, Characterization and Antifungal Activity Studies on Quinazoline-4-one Derivatives Containing 8-Hydroxy Quinazoline Ligand and its Metal Chelates - Vashi, R.T.; Shelat, C.D.; Patel, Himanshu (Asian Journal of Chemistry, 2010)
The novel ligand HL4 was synthesized from anthranilic acid. For this quinazoline-4-one 8- hydroxyquinoline (QHQ) condensed molecules were used. The transition metal chelates like Cu(II), Ni(II), Co(II), Mn(II) and Zn(II) with HL4 have been prepared and characterized by physicochemical methods such as elemental analysis, conductometric studies, magnetic susceptibility, IR, NMR and electronic spectral data. The stoichiometry of the complex has been found to be 1:2 (metal:ligand). An octahedral geometry around Co(II), Ni(II) and Mn(II), distorted octahedral geometry around Cu(II) and tetrahedral geometry around Zn(II) have been proposed. The antifungal activity of ligand and its metal chelates was screened against various fungi.